Nerve injuries about the elbow - Hariri, S.; McAdams, T. R. (Clinics in Sports Medicine, 2010)
The ulnar, radial, median, medial antebrachial cutaneous, and lateral antebrachial cutaneous nerves are subject to traction and compression in athletes who place forceful, repetitive stresses across their elbow joint. Throwing athletes are at greatest risk, and cubital tunnel syndrome (involving the ulnar nerve) is clearly the most common neuropathy about the elbow. The anatomy and innervation pattern of the nerve involved determines the characteristic of the neuropathy syndrome. The most important parts of the work-up are the history and physical examination as electrodiagnostic testing and imaging are often not reliable. In general, active rest is the first line of treatment. Tailoring the surgery and rehabilitation protocol according to the functional requirements of that athlete's sport(s) can help optimize the operative outcomes for recalcitrant cases.